Antimicrobial Efficacy of Nyctanthes arbor-tristis Linn. Leaf Extract against Common Pathogens of Sub-Clinical Mastitis in Cows - Deepraj; Singh, Jitendra P.; Singh, Satyavrat; Yadav, Dinesh K.; Ramakant; Niyogi, Debasish; Shrivastava, Dharam P.; Joshi, Rajesh K. (Indian Journal of Veterinary Sciences and Biotechnology, 2022)
This study was conducted during December 2020 to June 2021 by screening 200 cows for sub-clinical mastitis by using California mastitis test and Whiteside test, and the antimicrobial efficacy of Nyctanthes arbor-tristis Linn (Jasmine, Parijatha) leaves extract was studied against mastitis pathogens. The in vitro efficacy of aqueous and methanolic extract of Nyctanthes arbor-tristis leaves and its combination was studied against a positive control, i.e., antibiotic ciprofloxacin. The isolates of Streptococcus agalactiae showed maximum zone of inhibition against combination of aqueous and methanolic extract, while S. aureus and Escherichia coli showed maximum zone of inhibition against aqueous extract. The methanolic and aqueous extracts, and its combination of Nyctanthes arbor-tristis leaves had minimum inhibitory concentration (MIC) value 50 µg/mL and 25 µg/mL, against Streptococcus agalactiae and Staphylococcus aureus, respectively. The MIC values of methanolic and combination of both extracts against Escherichia coli was 50 µg/mL in comparison to aqueous extract, i.e., 12.5 µg/mL. The aqueous extract had minimum bactericidal concentration (MBC) against Streptococcus agalactiae as 100 µg/mL. In methanolic and combination extract of N. arbor-tristis the highest value of MBC obtained for Escherichia coli, and Streptococcus agalactiae was 50 µg/mL each.